A review of nutrition labeling and food choice in the United States - Alice Dumoitier; Vincent Abbo; Zachary T. Neuhofer; Brandon R. McFadden (Wiley, 2019)
Summary A proliferation of processed food and labeling claims motivated the Nutrition Labeling and Education Act of 1990, which mandated the Nutrition Facts Label. Providing nutrition information is often put forth as a way to change food choice; however, despite efforts to provide dietary information using nutrition labeling, more than a third of the US has obesity and portions of the population continue to under consume vital nutrients. There has been progress beyond the Nutrition Facts Label in recent years with front‐of‐package labeling and menu labeling, which is crucial given changes in consumption trends for food‐away‐from‐home. Additionally, changes were recently made to the Nutrition Facts Label due to lack of awareness, understanding, and ability to effectively improve diet quality. This paper explores the literature to track the evolution of knowledge about attention to nutrition information and how nutrition information affects dietary choices.